2000
DOI: 10.1063/1.1315358
|View full text |Cite
|
Sign up to set email alerts
|

Stable stratification alteration in a thermal diffusion cloud chamber

Abstract: Homogeneous nucleation rate measurements of 1-butanol in helium: A comparative study of a thermal diffusion cloud chamber and a laminar flow diffusion chamberThe influence of buoyant convection on the operation of the upward thermal diffusion cloud nucleation chamber J. Chem. Phys. 111, 8013 (1999); 10.1063/1.480274 Two-dimensional transport and wall effects in the thermal diffusion cloud chamber. II. Stability of operation J. Chem. Phys. 106, 624 (1997); 10.1063/1.473401 Two-dimensional transport and wall eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…However irregular roll patterns can be observed in a cylindrical container: the rolls arrange themselves naturally with their axis, whenever possible, perpendicular to the lateral boundary [21]. Indeed, Schaeffer et al [11] showed that the natural convection tends to increase maximum saturation. This is due to the fact that the Rayleigh-Bénard cells move the nucleation plane towards the upper plate.…”
Section: Numerical Results In the Convective Regimementioning
confidence: 97%
See 1 more Smart Citation
“…However irregular roll patterns can be observed in a cylindrical container: the rolls arrange themselves naturally with their axis, whenever possible, perpendicular to the lateral boundary [21]. Indeed, Schaeffer et al [11] showed that the natural convection tends to increase maximum saturation. This is due to the fact that the Rayleigh-Bénard cells move the nucleation plane towards the upper plate.…”
Section: Numerical Results In the Convective Regimementioning
confidence: 97%
“…Moreover, the heated chamber wall (the wall is heated to be kept clean of condensate) may cause a buoyancy driven convection that can propagate towards the center of the chamber and cause a motion of the gas mixture (Ferguson and Nuth [10]). These effects have been examined numerically by Schaeffer et al [11] who used a 2D mass, heat and momentum numerical model to show that the choice of the carrier gas within the TDCC is of importance since an inappropriate choice can alter the nucleation processes. Quite recently, Ferguson et al [12] performed a similar analysis with lower molecular weight gases and with an emphasis on the effect of the total pressure on the TDCC operation.…”
Section: Introductionmentioning
confidence: 98%
“…It is shown that the mathematical model allows to properly predict the evolutions of the gas mixture properties from an initial state up to a well defined steady-state. However, these computations clearly display that too sharp increases or decreases in the wall temperature may lead to local supersaturations which are admissible provided they do not exceed the critical supersaturation corresponding to the local temperature within the cavity [21][22][23]. Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a numerical procedure based on a finite volume method could not converge properly in the framework of this assumption since the global mass conservation of the mixture is not satisfied. Dufour and Soret effects are assumed negligibly small and there is no fog formation inside the cavity [15]. There are no chemical reactions, heat dissipation or heat generation, and the radiative heat transfer in the cavity is neglected.…”
Section: Mathematical Formulationmentioning
confidence: 99%